CHANGING EMPHASES IN SEXUALITY EDUCATION AMONG ADOLESCENCE - BABATUNDE, OBALASE STEPHEN; BOLANLE, OGBEYE GBEMISOLA; AKINTUNDE, SMART ADESEGHA (IJRDO- Journal of Educational Research, 2016)
The current study was designed to investigate the changing emphasis on sexuality education in Nigeria. This brings about consciousness and awareness in the subject matters. Despite various awareness programmes of sexuality education in the mass and electronic media young people engage in risky sexual behaviour for several reasons .Such reasons include the following: Economic factor, Cultural factors, Lack of adequate information, Poverty and Social consequences. The need to inform young people about the causes and consequences of uncontrolled rapid population growth has become paramount hence the National Population Policy of 1988 which was recently revised and officially launched in February 2005, was put in place with emphases on population education as a potential vehicle to translate the population Policy into action (Forrest & Silverman , 1989).Sexuality education is a process of learning about how an individual can be comfortable with all aspects of being human. Sexuality education can also be described as a process of providing information, skills and services that enables person to adopt safe sexual behaviours including abstainess, non-penetrative sex such as hugging, holding hands, as well as correct and consistent use of condom. Sexually healthy behaviours also include seeking care from trained health workers during incidence of any reproductive morbidity such as sexually transmitted infection (STIs), unwanted pregnancy and infertility (Adesokan, 2009).Sexuality Education has changed from traditional concept to modern concept .Increased Knowledge about sexuality matters. Attitudinal and Behavioural Change, Abstinence as the key for effective sexuality education, Emphasis on sexuality education bring about prevention of unwanted pregnancy, Increase Gender Equality and Prevention of Gender Violence. Emphasis on sexuality education bring about assertiveness skills, life and family building skills..The provision of sexual and reproductive health services for young people and the development of life-skills and sex education inside and outside of schools which center on the realities of young people’s lives and their needs , as expressed by adolescents themselves remain in an early stage.